Optimization of batch adsorption and fixed-bed adsorption of vanillin onto resin H103 - Abu Samah, Rozaimi (2016)
Vanillin is a widely used chemical especially in food and beverages industries. Its sweet odour also results in its application in perfumes and cosmetics industries. Traditionally, vanillin is produced by curing vanilla pods from vanilla plants. However, it is a very tedious and time-consuming process. It can also be produced chemically from several chemicals or intermediates, but the processes are either imposing an environmental issue (waste product), or dealing with high pressures and temperatures. Researchers are finding ways to produce vanillin via bioprocesses so it can be produced at slightly elevated temperature, by the act of certain microorganisms on several substrates from plant-based materials or biomass. However, due to its phenolic and aldehyde components in its molecular structure, vanillin can be toxic to the microorganisms when it is produced at certain concentration. Adsorption is one of the possible techniques to use for vanillin recovery from fermentation broth. However, the fermentation broth contains a variety of biomolecules that might interfere with the preliminary characterisation of the adsorbent. Therefore, researchers normally start the related works by using either an aqueous solution of the target biomolecule, continue with a simulated solution of fermentation broth, and finally test the characterised adsorbent with the actual fermentation broth containing the target product to be recovered. In this work, six adsorbent resins, namely Amberlite XAD-16, Amberlite XAD-2, Sepabeads SP207, Diaion HP-20, DM11 and H103, were tested for vanillin adsorption in aqueous solution. Other than Amberlite XAD-2 and DM11, the other resins gave more than 95% adsorption. For subsequent work, resin H103 was selected due to its high adsorption capacity of more than 98%, and its low purchasing price at approximately US$115 per kilogram. Vanillin adsorption using resin H103 was investigated based on five parameters, which were contact time (minute), resin dosage (g), pH, temperature (C), and vanillin initial concentration (mg/L). No large effect of vanillin adsorption within pH and temperature range tested. Thermodynamics data revealed that the adsorption process involved was an exothermic reaction, due to a negative sign of its enthalpy value. The magnitude of -17.956 kJ/mol also revealed that the adsorption of vanillin onto resin H103 was a physical adsorption. It was also revealed that the vanillin adsorption onto resin H103 followed a pseudo-second order kinetics, with values of constant parameters of qe of 10.684 mg/g and k2 of 0.006 g/mg.min. The linearized form gave a high determination coefficient (R2 = 0.995 for 0.5 g resin). Based on two most widely used isotherms (Langmuir and Freundlich), it was found that the former was slightly better fitted than the latter with an R2 value of 0.994. Subsequently, it was determined that the maximum capacity of resin H103 was 73.015 mg vanillin/g resin, and the Langmuir constant, KL, was determined to be 0.039 L/mg. Factorial screening was utilized to determine significant factors affecting the adsorption process. Each parameter was randomly subjected to 25 fractional factorial design for the identification of significant parameters, and subsequently optimized using response surface methodology (RSM). Sixteen experiments were carried out for the screening process, and 13 experiments for optimization. With the aid of Design Expert version 7.1.6 for statistical analysis, it was determined that vanillin initial concentration and resin dosage were significant factors affecting the vanillin adsorption onto resin H103 (determination coefficient value, or R2, of 0.9996). While the other insignificant factors were kept constant, the two significant factors were then subjected to an optimization process using response surface methodology. The tested range for optimization did not reveal any optimum level, despite its high R2 value of 0.9515. It was observed that the optimum point might fall outside the tested range. Further adsorption process via fixed bed mode was also investigated, with the aim of elucidating the dynamic adsorption behaviour of vanillin onto resin H103 packed in a column attached to ÄKTAexplorer 100 system. It was also used to describe the scaling analysis of a fixed bed adsorption column. Three parameters were investigated, which were bed height, vanillin initial concentration, and flow rate of the feed. Plots of effluent concentration versus time, or breakthrough curves, revealed that the fixed bed vanillin adsorption onto resin H103 can be described by both Bohart-Adams and Belter’s equation, with a high R2 of 0.9672. From the breakthrough curves, the dynamic adsorption capacities of the fixed bed were determined to be 96.813, 194.125, and 314.960 mg vanillin/g adsorbent, for bed heights of 5 cm, 10 cm, and 15 cm, respectively.